2013
DOI: 10.1111/jpy.12120
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of dinoflagellate polyketide synthases and fatty acid synthase activity

Abstract: Dinoflagellates are prolific producers of polyketide secondary metabolites. Dinoflagellate polyketide synthases (PKSs) have sequence similarity to Type I PKSs, megasynthases that encode all catalytic domains on a single polypeptide. However, in dinoflagellate PKSs identified to date, each catalytic domain resides on a separate transcript, suggesting multiprotein complexes similar to Type II PKSs. Here, we provide evidence through coimmunoprecipitation that single-domain ketosynthase and ketoreductase proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…Brevetoxins have also been demonstrated to aggregate into artificial lipid bilayers 29. Our findings contradict earlier localization studies: one which failed to identify brevetoxin in isolated chloroplasts by LC‐MS/MS,30 and a published abstract that reported that brevetoxins are located in secretory vesicles by using fluorescent anti‐brevetoxin antibodies 31. A follow‐up paper to the latter report has not yet appeared.…”
Section: Discussioncontrasting
confidence: 98%
“…Brevetoxins have also been demonstrated to aggregate into artificial lipid bilayers 29. Our findings contradict earlier localization studies: one which failed to identify brevetoxin in isolated chloroplasts by LC‐MS/MS,30 and a published abstract that reported that brevetoxins are located in secretory vesicles by using fluorescent anti‐brevetoxin antibodies 31. A follow‐up paper to the latter report has not yet appeared.…”
Section: Discussioncontrasting
confidence: 98%
“…brevis found the absence of Type II FAS, suggesting that K . brevis might possess a Type I FAS system or involve the role of PKS‐like domains for fatty acid synthesis (Van Dolah et al ., ). Kohli et al .…”
Section: Discussionmentioning
confidence: 97%
“…In a study performed by Van Dolah et al . (), antibodies developed for K . brevis PKSs were used to bind to similar proteins from a strain of O .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the common ancestor of apicomplexans and dinoflagellates must have had both forms. Although FAS in dinoflagellates is less well studied, these organisms can synthesize fatty acids de novo (39,40). Gene disruption of type II FAS in Plasmodium shows that this plastid pathway is essential during the liver stage and, in a human strain, the insect stage of the life cycle, implying that FAS might be a function mandating plastid retention (13,35,41).…”
mentioning
confidence: 99%
“…S1A). Polyketide syntases (PKS) are a related family of proteins that are considered degenerate FASs in which one or more modules have been lost, and PKS are known to occur in dinoflagellates (40). Although two of the transcripts contain all modules expected of complete type I FAS proteins, it is difficult to reliably discern FAS from PKS without biochemical validation.…”
mentioning
confidence: 99%